What drives the profitability of dairy processing firms in India? The results of decomposition analysis - Asha Devi S S; B S Chandel (Agricultural Economics Research Review, 2023)
We study the profitability growth in the organized dairy processing sector in India from 1993 to 2017. Using a parametric approach, we decompose the change in profitability into price and non-price factors. The total factor productivity (TFP) grew, driven mainly by improvements in technical efficiency and technical change. The output grew, too. The growth in TFP and output increased profitability at 5.90% per annum. The study also analyses performance by firm size and finds that large firms performed better in terms of profitability growth, mainly due to the growth in output and efficiency in use of inputs.